EFEK CIRI KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI INSTRINSIK ATAS PRESTASI KERJA PEGAWAI SERTA SIKAP PUAS PADA PEKERJAAN SEBAGAI VARIABEL MEDIASI - Anggraini, Nila; Saddewisasi, Wyati; Sugiarti, Rini (Jurnal Bina Manajemen, 2023)
A survey was conducted to test and analyze the effects of transformational leadership characteristics and intrinsic A survey was conducted to test and analyze the effects of transformational leadership characteristics and intrinsic motivation on employee work performance and satisfaction as a mediating variable on B.L.U.D employees at RA Kartini Hospital, Jepara Regency. The problem faced by RSUD RA Kartini Jepara Regency is that the Work Performance of B.L.U.D employees has not met the hospital's target. The survey was conducted and used quantitative procedures and analyzed and used SmartPLS 4. The community studied in this survey was all B.L.U.D employees at the R,A Kartini Hospital, Jepara Regency, totaling 410 employees. the sample used was 203 employees and the sample determination in this survey used Non Probability Sampling and the sampling technique was purposive sampling. The results of the analysis show that transformational leadership traits and intrinsic motivation have a positive and significant effect on job satisfaction and employee work performance. Satisfaction with work is able to mediate the effects of transformational leadership characteristics and intrinsic motivation on employee work performance. Following the Adjusted R Square value explains that transformational leadership characteristics, intrinsic motivation and a satisfied attitude at work affect employee work performance by 0.667 or 66.7% and the rest is explained by other variables outside the survey.